Pharmacotherapy for Infertility in Ghana: A Prospective Study on Prescription Patterns and Treatment Outcomes among Women undergoing Fertility Treatment - Stephen Mensah Arhin, PhD; Kwesi Boadu Mensah, PhD; Evans Kofi Agbeno, MBChB, PhD; Isaac Tabiri Henneh, PhD; Diallo Abdoul Azize, MBChB, PhD; Abigail Boateng, MBChB; Kwame Opoku-Agyeman, PhD; Charles Ansah, MPhil, PhD (Elsevier, 2023)
ABSTRACT: Background: Pharmacotherapy remains a first-line and major treatment option for couples struggling with infertility, especially in sub-Saharan Africa, where other expensive alternatives are rarely available. Despite the reliance on pharmacotherapy for treating infertility in the subregion, especially for those diagnosed with unexplained infertility, little is known about the actual influence of drug therapies on conception. Objectives: The study aimed to prospectively assess the prescription patterns and outcomes of pharmacotherapy for women undergoing fertility treatment in Ghana. Methods: This prospective cohort study involved 482 infertile women presenting for fertility treatment in 4 fertility clinics in the Cape Coast Metropolis of Ghana between March 2019 and February 2021. A simple random sampling technique was used to recruit subjects for the study. The women were followed up for 12 months to assess the outcome of drug therapy on conception. Data analysis was done using Stata version 14. Logistic regression was used to assess the association between trends with dichotomous outcomes. Results: The study identified that approximately 45.2% of the patients received monotherapy, whereas 24.1% received a combination of 2 drugs. Patients treated with a combination of 3 drugs were more likely to conceive (adjusted odds ratio = 4.10; 95% CI, 1.29-13.02; P = 0.02) than those without treatment. Conclusions: Patients treated with combination therapies had higher chances of conception than those without medications. However, a combination of nutritional and herbal therapies were associated with improved outcomes compared with conventional and nutritional supplements. The study's outcome could provide fertility specialists and stakeholders insight into choosing appropriate treatment options for prospective couples seeking fertility care. Consequently, fertility patients can access specific treatment options to meet their desired needs.